Strategi Pembiasaan Membaca Al Qur’an Pra Pembelajaran Untuk Kesiapan Mental Belajar Pada Siswa MA Manbaul Ulum Pati - Ka'anto, Ka'anto; Sepdianto, Mulyo; Zulyana, Lina; Mawadah, Irma Ikhdatun (AL-BURHAN, 2024)
This study aims to description of the strategy of habituation of reading the Qur'an before learning for the mental readiness of students' learning at MA Manbaul Ulum Pati and to find out the supporting and inhibiting factors of the strategy of habituation of reading the Qur'an before learning for the mental readiness of students' learning at MA Manbaul Ulum Pati. This type of research is case study research with a qualitative approach. Primary sources, namely: the principal, teachers, and students of MA Manbaul Ulum Pati. The data collection techniques used are (1) interviews (2) observation (3) documentation. While the data analysis techniques include: (1) data reduction (2) data presentation and (3) verification/conclusion. Research results 1) Pre-learning Al-Quran Reading Habitual Strategy for Mental Readiness to Learn in MA Manbaul Ulum Pati Students with enthusiasm, responsibility and discipline with the steps of Getting used to reading the Al-Quran from an early age, Doing the habit routinely every morning before KBM, Reading prayers before studying, Reading the Al-Quran together or in turns depending on the instructions of the teacher who enters the first lesson, Listening while correcting students' reading, Providing motivation while linking it to the wisdom of the verses being read, Reading the khataman quran prayer before ending this activity. 2) Supporting factors include the Foundation, Head of Madrasah, Budget policy, Dedication from teachers while inhibiting factors include noisy students, not following, being late, and not meeting the reading targets from their teachers.Keywords: Mental readiness to learn, Reading the Al-Quran, Habitual Strategy